PENGARUH KOMUNIKASI ORANG TUA TERHADAP MOTIVASI BERPRESTASI PADA SMP SWASTA RIAMA MEDAN - Zulmawati, Zulmawati (JGK (Jurnal Guru Kita), 2018)
Abstract : Effect of Parent Communication on Achievement Motivation (Study at Private Junior High School of Medan). The purpose of this study is to see the effect of parent communication on student achievement motivation in private junior Riama Medan. The form of the research is descriptive analysis, while the sample used in this research is 75 students of class VII, VIII and IX in Junior High School Private Riama Medan by using data collecting tool that is observation, questionnaire and interview. The results obtained from this study there is no influence between parent communication with achievement motivation in private junior Riama Medan. In accordance with the provisions if the value of r count is smaller than the value of r table (r arithmetic